Prevalence of Leptospira in murine in China: A systematic review and meta-analysis - Li, Jian-Ming; Li, Lian-Min; Shi, Jun-Feng; Li, Ting; Wang, Qi; Ma, Qing-Xia; Zheng, Wei; Feng, Hai-Feng; Liu, Fei; Du, Rui (Frontiers in Veterinary Science, 2022)
Leptospirosis is an acute infectious disease caused by pathogenic bacteria from the genus Leptospira. The disease is widely distributed throughout China, causing harm to human and animal health. Murine may naturally carry a variety of pathogenic Leptospira, thus being important sources of infection by humans and livestock. The aim of this study was to assess and analyse the prevalence of Leptospira and its risk factors in murine. We collected 46 publications published between inception and 2022 through China Knowledge Network (CNKI), VIP Chinese Journal Database, Wanfang Database, PubMed, and ScienceDirect. In these studies, a total of 54,051 murine in 5 regions of China were investigated, and the prevalence of leptospirosis ranged from1.11% to 35.29%. The prevalence of murine leptospirosis in south China was the highest, at 20.13%, and the lowest in northeast China, at 1.11% (P<0.05). The prevalence of leptospirosis in male murine was 21.38%, which was significantly higher than that in females (17.07%; P<0.05). Results according to detection method subgroup showed that the prevalence from serological testing was 15.94%, which was significantly higher than that of aetiology and molecular biology methods (P<0.01). In the sample subgroup, the positive rate of serum samples was 15.30%, which was significantly higher than that of tissue samples, at 7.97%. In addition, the influence of different geographical factors on prevalence was analysed, indicating that the Yangtze River Basin was a high-incidence area for leptospirosis. The study showed that Leptospira were ubiquitous throughout the country, and factors such as environment, temperature and landform affect the murine distribution and their bacteria carrying rate. We suggest strengthening the continuous monitoring of leptospirosis and taking effective and comprehensive measures such as reducing water contact, vaccinating in high-incidence seasons, and avoiding human contamination caused by water pollution and contact with infected murine.